The role of Re in effecting isothermal oxidation behavior of β-(Ni, Pt)Al coating on a Ni-based single crystal superalloy. (November 2020) - Li, W.; Fu, L.B.; Liu, Y.D.; Zhang, W.L.; Wang, T.G.; Jiang, S.M.; Gong, J.; Sun, C.
Highlights: 1Re-(Ni, Pt)Al coating was prepared by electroplating and arc ion plating. Adding Re reduced the oxidation rate and extent of β to γ′ phase degeneration. Doping Re in the coating had advantageous effects on the morphologies of TGO. The spallation and rumpling behavior of TGO could be relieved by Re doping. Formation of NiAl2 O4 spinel was avoided due to the existence of pure Ni layer. Abstract: Two β-(Ni, Pt)Al coatings with or without Re doping and a PtAl diffusion coating were prepared on a single crystal Ni-based superalloy. Isothermal oxidation behavior of all the coatings was investigated at 1100 ℃ for 300 h. The Re doped β-(Ni, Pt)Al coating possessed the best isothermal oxidation resistance because Re reduced the oxidation rate and extent of β to γ′ phase degeneration. The oxidation mechanism of the PtAl diffusion coating and advantageous roles of Re on the effect of the morphologies, anti-spallation and rumpling behavior of thermally grown oxide (TGO) were discussed as well.